Does Wikipedia matter? The effect of Wikipedia on tourist choices - Marit Hinnosaar; Toomas Hinnosaar; Michael Kummer; Olga Slivko (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
We analyze the impact of information on Wikipedia on tourists' choices for travel destinations. Our results suggest a strong observational correlation between the amount of content on Wikipedia and tourist overnight stays. We propose a check of whether this correlation is causal. For that, we introduce randomized exogenous variation to articles' content. While our treatment is strong enough to affect content on the treated pages positively, we find no statistically significant effect of this treatment on tourist overnight stays.
urn:nbn:de:bsz:180-madoc-405197; Is replaced by the following version: http://hdl.handle.net/10419/173092
Keywords: D29; D80; H41; J60; L17; 330; Wikipedia; randomized treatment; online content; tourist visits